Polyhydroxyalkanoate Decelerates the Release of Paclitaxel from Poly(lactic-co-glycolic acid) Nanoparticles - Si Yeong Lee; So Yun Kim; Sook Hee Ku; Eun Ji Park; Dong-Jin Jang; Sung Tae Kim; Seong-Bo Kim (Pharmaceutics, 2022)
Biodegradable nanoparticles (NPs) are preferred as drug carriers because of their effectiveness in encapsulating drugs, ability to control drug release, and low cytotoxicity. Although poly(lactide co-glycolide) (PLGA)-based NPs have been used for controlled release strategies, they have some disadvantages. This study describes an approach using biodegradable polyhydroxyalkanoate (PHA) to overcome these challenges. By varying the amount of PHA, NPs were successfully fabricated by a solvent evaporation method. The size range of the NPS ranged from 137.60 to 186.93 nm, and showed zero-order release kinetics of paclitaxel (PTX) for 7 h, and more sustained release profiles compared with NPs composed of PLGA alone. Increasing the amount of PHA improved the PTX loading efficiency of NPs. Overall, these findings suggest that PHA can be used for designing polymeric nanocarriers, which offer a potential strategy for the development of improved drug delivery systems for sustained and controlled release.